A high selective “Turn-Off” aminopyrene based cyclotriphosphazene fluorescent chemosensors for Fe3+/Cu2+ ions - Şenkuytu, Elif (Elsevier S.A., 2018)
In this current study, the new aminopyrene based cyclotriphosphazene chemosensors 6 and 7 have been successfully synthesized. The identity of all the synthesized cyclotriphosphazene compounds was proven by 1H, 31P NMR and MALDI-TOF mass spectrometry. The photophysical and metal sensing properties of the targeted compounds were determined in the presence of various metals (Li+, Na+, K+, Cs+, Mg2+, Ca2+, Ba2+, Mn2+, Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Cd2+, Al3+, Hg+, Zn2+) using fluorescence spectroscopy. The fluorescence titration results showed that compounds 6 and 7 can be used as fluorescent chemosensors with high selectivity and sensitivity for Cu2+ and Fe3+ ions. Also, the complex stoichiometry of the final cyclotriphosphazene chemosensors and Cu2+/Fe3+ ions was determined by a Job's plot. © 2020 Elsevier B.V., All rights reserved.
Keywords: 1-Aminopyrene; Cyclotriphosphazenes; Fe3+/Cu2+; Fluorescent chemosensor